The Impact Of Restrictions On Community Activities During The Covid-19 Pandemic On The Revenue Of Culiner Small And Medium Enterprises (Ukm) In The Kendari Beach Area, Punggaloba Sub-District, Kendari Barat District, Kendari City - Anjar Milliniman; Marsuki Iswandi; Lukman Yunus (International Journal of Technology and Education Research, 2023)
This research aims toanalyze the impact of restrictions on community activities during the Covid-19 pandemic on the income of micro, small and medium enterprises (SMEs) around Kendari Beach, Punggaloba Village, West Kendari District, Kendari City. determination of the sample using purposive sampling techniques used data using primary data and secondary data. Data collection is done by observation, interviews, documentation. And the analysis used is income analysis to analyze and answer problems from the impact of limiting community activities during the Covid-19 pandemic. 39,600,000/month and receipts during Covid-19 amounted to Rp. 289,000. 000/month while the income before Covid-19 in the Kendari beach area, Kendari City, was Rp. 21,230,000/month and income during Covid-19 is Rp. 10,830,000/month